Dynamic Capabilities: Evidence from Agriculture Cooperatives in Indonesia - Violinda, Q; ., Sunjian (KnE Social Sciences, 2018)
The growth cooperatives membership in Indonesia has led to a range of economic and business questions about how these cooperatives should be best organized and operated. One important question relating to cooperatives organization considering their rapid growth in number and size is the appropriate sizing of cooperatives for long-run economic viability. This paper aims at exploring contributions of dynamic capabilities and organizational culture in performance of agriculture cooperatives in Indonesia. This study use structural equation model (SEM) to explore a theoretical model which links various dynamic capabilities, organizational culture, competitive advantage and performance. Technical samples in this research are simple random sampling with a large sample of 241 agriculture cooperatives from five region in Indonesia . This study finds that both dynamic capability and organizational culture of the agriculture cooperatives in Indonesia contribute significant and positive effect to their competitive advantage as well. On the other hand, organizational culture in the Indonesian agriculture cooperatives provide positive effect solely to their performance; yet not for their performance which is in significantly affected by the dynamic capability. Keywords: Dynamic capabilities; organizational culture;competitive advantage; performance; agriculture, cooperatives.